2022
DOI: 10.1021/acsmaterialsau.2c00029
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Controlled Growth of Transition Metal Dichalcogenides by Chemical Vapor Deposition for Integrated Electronics

Abstract: In recent years, transition metal dichalcogenide (TMD)-based electronics have experienced a prosperous stage of development, and some considerable applications include field-effect transistors, photodetectors, and light-emitting diodes. Chemical vapor deposition (CVD), a typical bottom-up approach for preparing 2D materials, is widely used to synthesize large-area 2D TMD films and is a promising method for mass production to implement them for practical applications. In this review, we investigate recent progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 171 publications
0
24
0
Order By: Relevance
“…Additionally, the high reaction temperature and noble gas atmosphere required in CVD production processes result in higher costs compared to liquid phase-based synthesis methods. 57,59 Overall, despite these advances, there is still significant research that must be done to improve the fabrication techniques for 2D materials. In fact, it is still missing a method that include the production of 2D materials with both high quality and large lateral dimensions that is at the same time also scalable and cost-effective which remains a critical challenge.…”
Section: Top-down Approachmentioning
confidence: 99%
“…Additionally, the high reaction temperature and noble gas atmosphere required in CVD production processes result in higher costs compared to liquid phase-based synthesis methods. 57,59 Overall, despite these advances, there is still significant research that must be done to improve the fabrication techniques for 2D materials. In fact, it is still missing a method that include the production of 2D materials with both high quality and large lateral dimensions that is at the same time also scalable and cost-effective which remains a critical challenge.…”
Section: Top-down Approachmentioning
confidence: 99%
“…Two-dimensional (2D) semiconductors, such as transition metal dichalcogenides (TMDs), have drawn great attention in both fundamental research and practical applications because of their exceptional electronic and photonic properties, and rational tailoring of their electronic properties is crucial toward the functional engineering for various device applications. − Several tactics have been demonstrated to tune the electronic properties of TMDs, such as by intentionally doping foreign atomic species in TMDs − and growing laterally heterogeneous atomic layers during the syntheses. ,,,,, Efforts have also been made in a simple and noninvasive manner, that is, by using weakly coupled substrates, such as the surfaces of 2D materials themselves, to tune the electronic interaction at the TMD–substrate interfaces and thereby their electronic states . Relying on the exquisite tuning of this weak interaction, plenty of unconventional properties have been made possible, such as the superconductivity and correlated flat bands recently discovered in twisted graphene − and TMDs. − Noble metal surfaces are also capable of rendering relatively weak interaction with TMDs, which also have been demonstrated as a playground for both material synthesis and structural and/or electronic tailoring. − It is generally concluded that the electronic coupling between TMD and a metal surface is sensitive to their surface adsorption. ,,, For example, TMDs’ quasiparticle energy bandgap can be changed by the lattice reconstruction induced by the Au substrate .…”
mentioning
confidence: 99%
“…The band shift occurs at the phase boundaries within a lateral width of ∟0.5 nm, consistent with the spatial extent of atomic edges formed between different crystal surfaces. In-plane p-n homojunctions are established crossing the boundaries with a built-in electric field of ∟8.8 × 10 6 V¡cm –1 in between phase-I and -II, and ∟1.42 × 10 7 V¡cm –1 in between phase-I and -III, evaluated using (Δ E C + Δ E V )/2 d , where d is the width of the transition region ( d = ∟0.5 nm), nearly two orders of magnitude greater than conventional TMDCs’ lateral heterostructures. ,, …”
mentioning
confidence: 99%
See 2 more Smart Citations